Anti-corrosion bottom film as well as preparation method and application thereof
By adopting a combination structure of low friction layer, transition layer and adhesive layer in the anti-corrosion base film of the metal laminated plate, the problem of easy damage to the anti-corrosion base film during tiling forming is solved, and higher anti-corrosion and bonding are achieved The effect is simple and environmentally friendly.
Patent Information
- Application Number
- CN202411526354.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The anticorrosion base film of existing metal laminated plates is easily damaged during the tile forming process, resulting in a reduced anticorrosion performance.
Adopt anticorrosion bottom film consisting of a low friction layer, a transition layer and an adhesive layer. The low friction layer contains elastomer, a plastic and silicone masterbatch, and the transition layer and an adhesive layer contain maleic anhydride grafts and tackifying petroleum Resin, through the synergistic action of these layers, reduces the friction coefficient and improves corrosion resistance.
It effectively avoids damage to the anti-corrosion base film during tiling forming, improves the anti-corrosion and bonding effect of the metal coating plate, and has a simple process and does not require oily and water-based adhesives.
Smart Images

Figure CN119391313A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion base films and metal-coated plates, and in particular relates to a low-friction anti-corrosion base film, a preparation method of the anti-corrosion base film and application of the anti-corrosion base film in metal-coated plates. Background Art
[0002] Metal-faced laminate is a composite material made of polymer and metal plate, suitable for construction, transportation, industry and other fields, with the characteristics of anti-corrosion, light weight and durability. In particular, the corrosion resistance and easy processing properties of metal-faced laminate make it an ideal material for industrial and commercial building roofs.
[0003] At present, the lower surface of the metal coated plate is generally treated with a coating or a conventional anti-corrosion base film for anti-corrosion protection. However, when the metal coated plate with a coating or a conventional anti-corrosion base film is pressed into shape, the coating or the anti-corrosion base film is easily damaged by the mechanical parts of the tile pressing machine, and the damaged parts of the coating or the anti-corrosion base film will aggravate the reduction of the anti-corrosion performance.
[0004] For example, the patent application with publication number CN118269440A involves a thermoplastic polyolefin elastomer plastic steel tile and its preparation method, using a modified polyvinyl chloride film or a modified polyolefin film as an anti-corrosion bottom film. However, these two anti-corrosion bottom films are still prone to bottom film damage during the plastic steel tile pressing and molding process, and the damaged parts of the bottom film are prone to rust during the use of the plastic steel tile.
[0005] Another example is the patent with the announcement number CN115570864B, which involves a multifunctional film-coated board and its preparation method, in which graphene oxide and silicon micropowder are added to the anti-corrosion base film. The effect of graphene oxide and silicon micropowder on reducing the friction coefficient of the anti-corrosion base film is very limited, and the anti-corrosion base film in the patent is also prone to base film damage during the film-coated board tile forming process.
[0006] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention
[0007] In view of this, in order to overcome the defects of the prior art, the purpose of the present invention is to provide an improved anti-corrosion base film, which has a low friction layer, and the low friction layer can further synergistically enhance the anti-corrosion and bonding effects.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions: A corrosion-resistant base film comprises a low-friction layer, a transition layer and an adhesive layer in sequence, wherein the adhesive layer is used for bonding with a metal plate; the low-friction layer comprises an elastomer, a plasticizer and a silicone masterbatch; the low-friction layer is used for reducing the friction coefficient of the corrosion-resistant base film and for improving the corrosion-resistant performance of the corrosion-resistant base film.
[0009] According to some preferred implementation aspects of the present invention, the low friction layer comprises the following raw material components in parts by weight: Elastomer 5~95 parts Plastic 5~95 parts 5~40 parts of silicone masterbatch.
[0010] Preferably, the mass ratio of the plastomer to the elastomer is 2:1 to 3:1, and the mass ratio of the plastomer to the silicone masterbatch is 4:1 to 5:1.
[0011] According to some preferred implementation aspects of the present invention, the low friction layer comprises the following raw material components in parts by weight: Elastomer 10~40 parts Plastic 20~80 parts 10~25 parts of silicone masterbatch.
[0012] According to some preferred embodiments of the present invention, the elastomer is a polyolefin elastomer, such as a propylene-based elastomer, preferably a polypropylene elastomer.
[0013] According to some preferred embodiments of the present invention, the plastomer is a polyolefin plastomer, such as polypropylene and / or HDPE (high-density polyethylene).
[0014] According to some preferred embodiments of the present invention, the carrier of the silicone masterbatch is one or more selected from high-density polyethylene, polystyrene such as SEBS, low-density polyethylene and propylene-based elastomer.
[0015] According to some preferred implementation aspects of the present invention, the adhesive layer includes maleic anhydride grafted EVA, maleic anhydride grafted polyolefin plastomer, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted polystyrene elastomer, tackifying petroleum resin, and polystyrene elastomer. The maleic anhydride grafted material mainly functions to provide bonding performance with the metal plate, and the tackifying petroleum resin and polystyrene elastomer mainly function to adjust the interface wetting performance when the anti-corrosion base film is hot-pressed and laminated with the metal plate.
[0016] According to some preferred implementation aspects of the present invention, the adhesive layer comprises the following raw material components in parts by weight: Maleic anhydride grafted EVA 5~95 parts Maleic anhydride grafted polyolefin plastomer 5~95 parts Maleic anhydride grafted polyolefin elastomer 5~50 parts Maleic anhydride grafted polystyrene elastomer 5-30 parts 5~20 parts of tackifying petroleum resin 5-35 parts of polystyrene elastomer.
[0017] Preferably, the adhesive layer comprises the following raw material components in parts by weight: Maleic anhydride grafted EVA 20~80 parts Maleic anhydride grafted polyolefin plastomer 20~60 parts Maleic anhydride grafted polyolefin elastomer 5~20 parts Maleic anhydride grafted polystyrene elastomer 5~10 parts 5~10 parts of tackifying petroleum resin 5-25 parts of polystyrene elastomer.
[0018] According to some preferred implementation aspects of the present invention, the content of VA (vinyl acetate) in the maleic anhydride grafted EVA (ethylene-vinyl acetate copolymer) is not higher than 28%, which is beneficial to improving the adhesion of the anti-corrosion base film to the metal plate and the molding of the base film; the maleic anhydride grafted polyolefin plastomer is maleic anhydride grafted linear low-density polyethylene (LLDPE); the maleic anhydride grafted polyolefin elastomer is maleic anhydride grafted POE; the maleic anhydride grafted polystyrene elastomer is maleic anhydride grafted SEBS (hydrogenated styrene-butadiene block copolymer) or maleic anhydride grafted HIPS (high impact polystyrene); the tackifying petroleum resin is hydrogenated petroleum resin; the polystyrene elastomer is SIS (styrene-isoprene-styrene block copolymer), SBS (styrene-butadiene-styrene block copolymer), SEBS (a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenating polybutadiene as the middle elastic block) or HIPS (high impact polystyrene).
[0019] According to some preferred embodiments of the present invention, the transition layer comprises a polyolefin elastomer, a polyolefin plastomer and a maleic anhydride graft, wherein the maleic anhydride graft is optional.
[0020] According to some preferred implementation aspects of the present invention, the transition layer comprises the following raw material components in parts by weight: Polyolefin elastomer 10~75 parts Polyolefin plastomer 10~75 parts Maleic anhydride grafted material 0-50 parts.
[0021] Preferably, the transition layer comprises the following raw material components in parts by weight: Polyolefin elastomer 20~60 parts Polyolefin plastomer 20~60 parts 10-30 parts of maleic anhydride grafted compound.
[0022] According to some preferred embodiments of the present invention, the polyolefin elastomer is one or more selected from polypropylene elastomer and polyethylene elastomer; the polyolefin plastomer is one or more selected from polypropylene plastomer and polyethylene plastomer; the maleic anhydride grafted product is one or more selected from maleic anhydride grafted polyethylene, polypropylene, POE (a random copolymer elastomer obtained by in-situ polymerization of ethylene and high carbon α-olefins such as 1-butene, 1-hexene, 1-octene, etc. using a metallocene catalyst), EVA (ethylene-vinyl acetate copolymer), SIS (styrene-isoprene-styrene block copolymer), SEBS (a linear triblock copolymer with polystyrene as the terminal segment and an ethylene-butene copolymer obtained by hydrogenating polybutadiene as the middle elastic block).
[0023] According to some preferred embodiments of the present invention, the low friction layer also includes an additive, which includes an antioxidant and / or a UV absorber; the antioxidant is one or more selected from antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 264; the UV absorber is one or more selected from UV327, UV531, UV770, and UV944.
[0024] According to some preferred embodiments of the present invention, the thickness of the anti-corrosion base film is 30-200 um, preferably 40-120 um, and most preferably 60-100 um. The friction coefficient of the low friction layer side of the anti-corrosion base film is 0.19-0.35.
[0025] The polysiloxane in the silicone masterbatch of the low friction layer is a hybrid material composed of an inorganic siloxane main chain with an organic group side chain, and the nano-silicon dioxide in the silicone masterbatch is also an inorganic component. The synergistic effect between the inorganic and organic components in the low friction layer increases the anti-corrosion effect of the base film. At the same time, through the selection of materials for the above-mentioned low friction layer, transition layer, and bonding layer, such as the maleic anhydride grafted EVA in the transition layer has better compatibility with the main resin in the low friction layer and the bonding layer, the anti-corrosion base film has a higher cohesive strength, which further improves the salt spray resistance.
[0026] The present invention also provides a method for preparing the anti-corrosion base film as described above, comprising the following steps: The raw materials of the low friction layer, the raw materials of the transition layer and the raw materials of the bonding layer are extruded and granulated respectively; The particles after extrusion granulation are passed through a film blowing machine to prepare a three-layer composite film, which is the anti-corrosion base film.
[0027] In some embodiments, a method for preparing an anti-corrosion base film comprises the following steps: The raw materials of the low friction layer are added to the twin-screw extruder for granulation, and the extrusion temperature is 140-200℃; The raw materials of the transition layer film are added to a twin-screw extruder for granulation preparation, and the extrusion temperature is 150-200°C; The raw materials for the metal bonding layer are added to a twin-screw extruder for granulation preparation, and the extrusion temperature is 130-190°C; The granules prepared by granulation of the twin-screw extruder are passed through a three-layer film blowing machine to prepare a three-layer composite hot melt adhesive film, namely the anti-corrosion base film. The co-extrusion die head temperature is 140-190°C.
[0028] The present invention also provides an application of the anti-corrosion base film as described above in metal-coated panels, namely, comprising metal-coated panels prepared with the anti-corrosion base film as described above. Furthermore, the anti-corrosion base film or metal-coated panels can be prepared into building roofs.
[0029] Preferably, the metal film-coated board comprises an anti-corrosion base film, a metal plate, a hot melt adhesive film and a waterproof coiled material in sequence. The metal plate is an aluminum-zinc-coated steel plate. The metal film-coated board can be subsequently formed into a building roof by pressing tiles. The salt spray resistance of the metal film-coated board is that no red rust occurs for at least 1600 hours or even 4000 hours.
[0030] Compared with the existing traditional technology, the advantages of the present invention are: the anti-corrosion base film of the present invention has a low friction coefficient, which can avoid damage when used for metal coated panels to press tiles, and can further improve the anti-corrosion effect; the production process is simple, one-time molding, no need to use oily and water-based adhesives, and all production is completed using polymer materials; it has the characteristics of being resistant to wear of press tile machines, strong adhesion to metal plates, and excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 It is a schematic diagram of the cross-sectional structure of the anti-corrosion base film in a preferred embodiment of the present invention; Figure 2 Schematic diagram of the cross-sectional structure of a metal-clad plate in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0034] The sources of the raw materials used in the following examples are as follows:
[0035] like Figure 1 As shown, the three-layer anti-corrosion base membrane of this embodiment includes a low-friction layer exposed on the lowermost surface, an adhesive layer bonded to the metal plate, and a transition layer connecting the low-friction layer and the adhesive layer.
[0036] The low friction layer is composed of elastomer wear-resistant agent, plastomer wear-resistant agent, silicone masterbatch and additives. The dosage of various components in the low friction layer can be determined according to the needs of the tile type. The mass ratio of plastomer to elastomer is 2:1~3:1, and the mass ratio of plastomer to silicone masterbatch is 4:1~5:1.
[0037] The low friction layer comprises the following raw material components by weight: Elastomer 5~95 parts Plastic 5~95 parts 5~40 parts of silicone masterbatch.
[0038] Preferably, the low friction layer comprises the following raw material components by weight: Elastomer 10~40 parts Plastic 20~80 parts 10~25 parts of silicone masterbatch.
[0039] The elastomer is a polyolefin elastomer, such as a propylene-based elastomer, preferably a polypropylene elastomer; the plastomer is a polyolefin plastomer, such as polypropylene and / or HDPE (high-density polyethylene); and the silicone masterbatch is a silicone masterbatch formed with high-density polyethylene, polystyrene, low-density polyethylene or a propylene-based elastomer as a carrier.
[0040] The auxiliary agent includes an antioxidant and / or an ultraviolet absorber; the antioxidant is one or more selected from antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 264; the ultraviolet absorber is one or more selected from UV327, UV531, UV770, and UV944.
[0041] The adhesive layer includes maleic anhydride grafted EVA, maleic anhydride grafted polyolefin plastomers, maleic anhydride grafted polyolefin elastomers, maleic anhydride grafted polystyrene elastomers, tackified petroleum resins and polystyrene elastomers. The maleic anhydride grafted material mainly provides adhesion to the metal plate, while the tackified petroleum resins and polystyrene elastomers mainly regulate the interfacial wetting properties of the anticorrosive base film and the metal plate during hot pressing.
[0042] The adhesive layer includes the following raw material components by weight: Maleic anhydride grafted EVA 5~95 parts Maleic anhydride grafted polyolefin plastomer 5~95 parts Maleic anhydride grafted polyolefin elastomer 5~50 parts Maleic anhydride grafted polystyrene elastomer 5-30 parts 5~20 parts of tackifying petroleum resin 5-35 parts of polystyrene elastomer.
[0043] Preferably, the adhesive layer comprises the following raw material components by weight: Maleic anhydride grafted EVA 20~80 parts Maleic anhydride grafted polyolefin plastomer 20~60 parts Maleic anhydride grafted polyolefin elastomer 5~20 parts Maleic anhydride grafted polystyrene elastomer 5~10 parts 5~10 parts of tackifying petroleum resin 5-25 parts of polystyrene elastomer.
[0044] Among them, the content of VA (vinyl acetate) in maleic anhydride grafted EVA (ethylene-vinyl acetate copolymer) is not more than 28%, which is beneficial to improving the adhesion of the anti-corrosion base film to the metal plate and the molding of the base film; the maleic anhydride grafted polyolefin plastomer is maleic anhydride grafted linear low-density polyethylene; the maleic anhydride grafted polyolefin elastomer is maleic anhydride grafted POE; the maleic anhydride grafted polystyrene elastomer is maleic anhydride grafted SEBS (hydrogenated styrene-butadiene block copolymer) or maleic anhydride grafted HIPS (high impact polystyrene); the tackifying petroleum resin is hydrogenated petroleum resin; the polystyrene elastomer is SIS (styrene-isoprene-styrene block copolymer), SBS (styrene-butadiene-styrene block copolymer), SEBS (linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block) or HIPS (high impact polystyrene).
[0045] The transition layer includes polyolefin elastomer, polyolefin plastomer, and selectively adds maleic anhydride grafted material. Its main function is to firmly bond the low friction layer and the metal bonding layer together when the anti-corrosion base film is formed, and to provide the overall cohesive strength of the low film.
[0046] The transition layer comprises the following raw material components by weight: Polyolefin elastomer 10~75 parts Polyolefin plastomer 10~75 parts Maleic anhydride grafted material 0-50 parts.
[0047] Preferably, the transition layer comprises the following raw material components by weight: Polyolefin elastomer 20~60 parts Polyolefin plastomer 20~60 parts 10-30 parts of maleic anhydride grafted compound.
[0048] Among them, the polyolefin elastomer is one or more selected from polypropylene elastomer and polyethylene elastomer; the polyolefin plastomer is one or more selected from polypropylene plastomer and polyethylene plastomer; the maleic anhydride grafted product is one or more selected from maleic anhydride grafted polyethylene, polypropylene, POE (a random copolymer elastomer obtained by in-situ polymerization of ethylene and high carbon α-olefins such as 1-butene, 1-hexene, 1-octene, etc. using a metallocene catalyst), EVA (ethylene-vinyl acetate copolymer), SIS (styrene-isoprene-styrene block copolymer), SEBS (a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block).
[0049] The anti-corrosion base film can be produced by casting, laminating or blowing film. When the blowing film process is used for production, the specific preparation process is as follows: The raw materials of the outer layer film are added to the twin-screw extruder for granulation, and the extrusion temperature is 140-200℃; The raw materials of the transition layer film are added to a twin-screw extruder for granulation preparation, and the extrusion temperature is 150-200°C; The raw materials of the inner layer film are added to a twin-screw extruder for granulation preparation, and the extrusion temperature is 130-190°C; The granules prepared by granulation with a twin-screw extruder are passed through a three-layer film blowing machine to prepare a three-layer composite film, and the co-extrusion die head temperature is 140-190°C.
[0050] The thickness of the anti-corrosion base film is 30-200um, preferably 40-120um, and most preferably 60-100um. The friction coefficient of the low friction layer side of the anti-corrosion base film is 0.19-0.35. When the anti-corrosion base film is applied to the metal coated plate, its salt spray resistance is at least 1600h without red rust.
[0051] Example 1 The anti-corrosion base film in this embodiment includes a low-friction layer exposed on the lowermost surface, an adhesive layer bonded to the metal plate, and a transition layer connecting the low-friction layer and the adhesive layer.
[0052] Among them, the raw materials of the low friction layer include, by weight: 60 parts of high-density polyethylene, 25 parts of polypropylene elastomer, and 15 parts of silicone masterbatch with SEBS as the carrier.
[0053] In parts by weight, the raw materials of the transition layer include: 40 parts of high-density polyethylene, 35 parts of polypropylene elastomer, and 25 parts of maleic anhydride grafted EVA.
[0054] By weight, the raw materials of the adhesive layer include: 40 parts of maleic anhydride grafted EVA, 30 parts of maleic anhydride grafted LLDPE, 10 parts of maleic anhydride grafted POE, 8 parts of maleic anhydride grafted SEBS, 6 parts of C5 petroleum resin, and 6 parts of HIPS.
[0055] Example 2 The anti-corrosion base film in this embodiment includes a low friction layer, a transition layer and an adhesive layer in sequence.
[0056] Among them, the raw materials of the low friction layer include, by weight: 65 parts of high-density polyethylene, 30 parts of polypropylene elastomer, and 15 parts of silicone masterbatch with SEBS as the carrier.
[0057] The raw material components of the transition layer and the bonding layer are the same as those in Example 1.
[0058] Example 3 The anti-corrosion base film in this embodiment includes a low friction layer, a transition layer and an adhesive layer in sequence.
[0059] The raw material composition of the low friction layer is the same as that of Example 1.
[0060] By weight, the raw materials of the transition layer include: 60 parts of high-density polyethylene, 15 parts of polypropylene elastomer, and 25 parts of maleic anhydride grafted EVA.
[0061] The raw material composition of the adhesive layer is the same as that of Example 1.
[0062] Example 4 The anti-corrosion base film in this embodiment includes a low friction layer, a transition layer and an adhesive layer in sequence.
[0063] The raw materials of the low friction layer include, by weight: 60 parts of high-density polyethylene, 25 parts of polypropylene elastomer, and 15 parts of silicone masterbatch with HDPE as the carrier.
[0064] The raw material components of the transition layer and the bonding layer are the same as those in Example 1.
[0065] Example 5 The anti-corrosion base film in this embodiment includes a low friction layer, a transition layer and an adhesive layer in sequence.
[0066] The raw material ratio of the low friction layer is: 60 parts of high-density polyethylene, 25 parts of polypropylene elastomer, and 15 parts of silicone masterbatch with LLDPE as the carrier.
[0067] The raw material components of the transition layer and the bonding layer are the same as those in Example 1.
[0068] Comparative Example 1 The anti-corrosion base film in this comparative example is different from that in Example 1 in that the polypropylene elastomer in the low friction layer is completely replaced with POE (a random copolymer elastomer achieved by in-situ polymerization of ethylene and high-carbon α-olefins such as 1-butene, 1-hexene, 1-octene, etc. using a metallocene catalyst), and the rest is basically the same as in Example 1.
[0069] Comparative Example 2 The anti-corrosion base film in this comparative example is different from that in Example 1 in that the maleic anhydride grafted EVA (ethylene-vinyl acetate copolymer) in the transition layer is completely replaced with maleic anhydride grafted LLDPE (linear low-density polyethylene), and the rest is basically the same as in Example 1.
[0070] Comparative Example 3 The anti-corrosion base film in this comparative example is different from that in Example 1 in that in this comparative example, all the silicone masterbatches in the low friction layer are replaced with HIPS (high impact polystyrene), and the rest is basically the same as in Example 1.
[0071] Comparative Example 4 The anti-corrosion base film in this comparative example is different from that in Example 1 in that in this comparative example, all the silicone masterbatches in the low friction layer are replaced with ultra-high molecular weight polyethylene, and the rest is basically the same as in Example 1.
[0072] Comparative Example 5 The anti-corrosion base film in this comparative example is different from that in Example 1 in that the low friction layer in this comparative example is composed of 45 parts of high-density polyethylene, 25 parts of polypropylene elastomer, and 30 parts of silicone masterbatch with SEBS as the carrier, and the rest is basically the same as in Example 1.
[0073] Comparative Example 6 The anticorrosive base film in this comparative example is different from that in Example 1 in that the transition layer is eliminated and the low friction layer and the adhesive layer are retained. The rest is basically the same as in Example 1.
[0074] Example 6 (Preparation of Metal-Coated Plate) The above-mentioned anti-corrosion base film is applied to the metal-coated plate, which comprises the anti-corrosion base film, the metal plate, the hot-melt adhesive film and the waterproof coiled material in sequence.
[0075] The production conditions are: hot pressing temperature 200℃, pressure 0.6MPa, hot pressing time 20s, TPO waterproofing membrane thickness 0.8mm, metal plate uses 0.6mm thick aluminum-zinc steel plate, coating weight 150g / m 2 .
[0076] The prepared metal-clad plate has a salt spray resistance of at least 1600 hours without the appearance of red rust.
[0077] Tests and Results The friction coefficient of the anti-corrosion base film was tested according to GB / T10006. At the same time, the anti-corrosion base films of Examples 1 to 5 and Comparative Examples 1 to 4 were bonded to metal plates to form metal-coated panels using the method of Example 6. The salt spray resistance performance of the lower surface of the metal-coated panels was tested according to GB / T10125. At the same time, the obtained metal-coated panels were pressed into tiles to form building roofs to observe whether they would be damaged during the pressing process. The test results are shown in Table 1 below:
[0078] The data of Example 1 and Comparative Example 1 show that polypropylene elastomer is easier to form a synergistic effect of salt spray resistance with high-density polyethylene and silicone masterbatch than POE elastomer. The data of Example 1 and Comparative Example 2 show that the maleic anhydride grafted EVA in the transition layer has better compatibility with the main resin in the low friction layer and the adhesive layer, the anti-corrosion base film has a higher cohesive strength and better salt spray resistance. The test data of Example 1 and Comparative Example 3 show that without the use of silicone masterbatch, the friction coefficient of the base film is higher and no synergistic effect of salt spray resistance is produced. The test data of Example 1 and Comparative Example 4 show that although the friction coefficient of the anti-corrosion base film using ultra-high molecular weight polyethylene as a component of the low friction layer is lower, no synergistic effect of salt spray resistance is produced. The test data of Example 1 and Comparative Example 5 show that increasing the amount of silicone masterbatch can reduce the friction coefficient of the anti-corrosion base film, but also reduce the salt spray resistance of the anti-corrosion base film, and there is a suitable ratio between the components in the low friction layer to produce synergistic benefits. The test data of Example 1 and Comparative Example 6 show that eliminating the transition layer of the anti-corrosion base film reduces the cohesive strength of the anti-corrosion base film, causing damage to the compression tile, thereby also reducing the salt spray resistance of the anti-corrosion base film.
[0079] The anti-corrosion base film of the present invention has a low friction coefficient, excellent corrosion resistance and can be compounded with a metal plate, and comprises a low friction layer, a transition layer and an adhesive layer for the metal plate in sequence. The adhesive layer of the anti-corrosion base film of the present invention can bond and compound the base film with the metal plate. The low friction layer of the base film can ensure that the metal coated plate will not be damaged during tile pressing and forming, improve the anti-corrosion performance of the polymer coating layer of the metal coated plate, and can be applied to the internal use environment of industrial plants with high requirements for anti-corrosion performance. Compared with the prior art, the advantages of the present invention are: 1. The low friction layer of the base film can overcome the disadvantage that the coating or conventional anti-corrosion base film is easily damaged during tile pressing and forming of the metal coated plate; 2. The metal adhesive layer of the base film can form a reliable bonding strength after hot pressing and compounding with the metal plate, eliminating the use of glue, being environmentally friendly and having a simple process; 3. The low friction component in the base film can produce a synergistic effect with other polymers in the base film, thereby improving the anti-corrosion performance of the overall structure of the base film.
[0080] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-corrosion base film, characterized in that: It includes a low friction layer, a transition layer and an adhesive layer in sequence, wherein the adhesive layer is used for bonding with the metal plate; the low friction layer includes an elastomer, a plasticizer and a silicone masterbatch; the low friction layer is used for reducing the friction coefficient of the anti-corrosion base film and for improving the anti-corrosion performance of the anti-corrosion base film.
2. The anti-corrosion base film according to claim 1, characterized in that: The mass ratio of the plastic body to the elastomer is 2:1 to 3:
1.
3. The anti-corrosion base film according to claim 1, characterized in that: The mass ratio between the plastomer and the silicone masterbatch is 4:1-5:
1.
4. The anticorrosive base film according to claim 1, characterized in that: The low friction layer comprises the following raw material components by weight: Elastomer 5~95 parts Plastic 5~95 parts 5~40 parts of silicone masterbatch.
5. The anti-corrosion base film according to claim 4, characterized in that: The low friction layer comprises the following raw material components by weight: Elastomer 10~40 parts Plastic 20~80 parts 10~25 parts of silicone masterbatch.
6. The anticorrosive base film according to claim 1, characterized in that: The elastomer is a polyolefin elastomer.
7. The anticorrosive base film according to claim 1, characterized in that: The plastomer is a polyolefin plastomer.
8. The anticorrosive base film according to claim 1, characterized in that: The carrier of the silicone masterbatch is one or more selected from high-density polyethylene, polystyrene, low-density polyethylene and propylene-based elastomer.
9. The anticorrosive base film according to claim 1, characterized in that: The adhesive layer comprises maleic anhydride grafted EVA, maleic anhydride grafted polyolefin plastomer, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted polystyrene elastomer, tackifying petroleum resin and polystyrene elastomer.
10. The anticorrosive base film according to claim 1 or 9, characterized in that: The adhesive layer comprises the following raw material components in parts by weight: Maleic anhydride grafted EVA 5~95 parts Maleic anhydride grafted polyolefin plastomer 5~95 parts Maleic anhydride grafted polyolefin elastomer 5~50 parts Maleic anhydride grafted polystyrene elastomer 5-30 parts 5~20 parts of tackifying petroleum resin 5-35 parts of polystyrene elastomer.
11. The anticorrosive base film according to claim 10, characterized in that: The adhesive layer comprises the following raw material components in parts by weight: Maleic anhydride grafted EVA 20~80 parts Maleic anhydride grafted polyolefin plastomer 20~60 parts Maleic anhydride grafted polyolefin elastomer 5~20 parts Maleic anhydride grafted polystyrene elastomer 5~10 parts 5~10 parts of tackifying petroleum resin 5-25 parts of polystyrene elastomer.
12. The anticorrosive base film according to claim 9, characterized in that: The content of VA in the maleic anhydride grafted EVA is not higher than 28%; the maleic anhydride grafted polyolefin plastomer is maleic anhydride grafted linear low-density polyethylene; the maleic anhydride grafted polyolefin elastomer is maleic anhydride grafted POE; the maleic anhydride grafted polystyrene elastomer is maleic anhydride grafted SEBS or maleic anhydride grafted HIPS; the tackifying petroleum resin is hydrogenated petroleum resin; the polystyrene elastomer is SIS, SBS, SEBS or HIPS.
13. The anticorrosive base film according to claim 1, characterized in that: The transition layer comprises a polyolefin elastomer and a polyolefin plastomer; the polyolefin elastomer is one or more selected from polypropylene elastomer and polyethylene elastomer; the polyolefin plastomer is one or more selected from polypropylene plastomer and polyethylene plastomer.
14. The anticorrosive base film according to claim 13, characterized in that: The transition layer comprises the following raw material components by weight: Polyolefin elastomer 10~75 parts Polyolefin plastomer 10~75 parts Maleic anhydride grafted material 0-50 parts.
15. The anti-corrosion base film according to claim 14, characterized in that: The transition layer comprises maleic anhydride grafts; the maleic anhydride grafts are one or more selected from maleic anhydride grafted polyethylene, polypropylene, POE, EVA, SIS, and SEBS.
16. The anticorrosive base film according to claim 14, characterized in that: The transition layer comprises the following raw material components by weight: Polyolefin elastomer 20~60 parts Polyolefin plastomer 20~60 parts 10-30 parts of maleic anhydride grafted material.
17. The anticorrosive base film according to claim 1, characterized in that: The low friction layer also includes an additive, which includes an antioxidant and / or an ultraviolet absorber; the antioxidant is one or more selected from antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 264; the ultraviolet absorber is one or more selected from UV327, UV531, UV770, and UV944.
18. The anticorrosive base film according to claim 1, characterized in that: The thickness of the anti-corrosion base film is 30-200 um, and the friction coefficient of the low friction layer side of the anti-corrosion base film is 0.19-0.
35.
19. A method for preparing an anticorrosive base film according to any one of claims 1 to 18, characterized in that: The steps include: The raw materials of the low friction layer, the raw materials of the transition layer and the raw materials of the bonding layer are extruded and granulated respectively; The particles after extrusion granulation are prepared by casting, laminating or blowing to obtain a three-layer composite film, which is the anti-corrosion base film.
20. Use of the anti-corrosion base film according to any one of claims 1 to 18 in metal-clad panels.
21. A metal-clad plate, characterized in that: The metal-coated plate comprises, in sequence, the anti-corrosion base film as described in any one of claims 1 to 18, a metal plate, a hot-melt adhesive film and a waterproof membrane.
22. The metal-clad plate according to claim 21, characterized in that: The metal film-clad plate has a salt spray resistance of at least 1600 hours without red rust.
Citation Information
Patent Citations
Thermoplastic polyolefin elastomer plastic steel tile and preparation method thereof
CN118269440A
Medical non-polyvinyl chloride composite transfusion hose
CN102218169A
SEBS carrier silicone master batch and preparation method thereof
CN115926361A
Easy-to-clean coiled material, self-adhesive coiled material and metal film-coated plate
CN118834616A
Cited By
Anti-corrosion base film, and preparation method therefor and use thereof
WO2026092378A1